Impact of Pancreatitis-Associated Protein on Newborn Screening Outcomes and Detection of CFTR-Related Metabolic Syndrome (CRMS)/Cystic Fibrosis Screen Positive, Inconclusive Diagnosis (CFSPID): A Monocentric Prospective Pilot Experience - Chiara Bianchimani; Daniela Dolce; Claudia Centrone; Silvia Campana; Novella Ravenni; Tommaso Orioli; Erica Camera; Gianfranco Mergni; Cristina Fevola; Paolo Bonomi; Giovanni Taccetti; Vito Terlizzi (MDPI AG, 2022)
Pancreatitis-Associated Protein (PAP)-based Cystic Fibrosis (CF) newborn bloodspot screening (NBS) protocols detect less CFTR-Related Metabolic Syndrome (CRMS)/CF Screen Positive, Inconclusive Diagnosis (CFSPID). We prospectively evaluated the impact of PAP as the second step of the CF NBS protocol, before the CFTR genetic analysis, on NBS outcomes and CRMS/CFSPID detection in the Tuscany region, Italy. In parallel to the usual protocol (IRT/DNA, protocol 1), PAP was analyzed in IRT-positive infants (IRT/PAP/DNA, protocol 2) from 1 June 2020 until 31 May 2022. We defined an infant as NBS positive if PAP was >1.8 μg/L for IRT value 99th percentile-100 μg/L or >0.6 μg/L for IRT value >100 μg/L. To increase the positive predictive value (PPV) of protocol 2, we retrospectively lowered the upper IRT range value from 100 to 90 μg/L (modified protocol 2). We identified 8 CF and 13 CRMS/CFSPID with protocol 1, 5 CF and 5 CRMS/CFSPID with protocol 2 and 8 CF and 5 CRMS/CFSPID with modified protocol 2. With the PAP-based protocols, we observed a reduction of sweat tests, healthy carrier detection and a significant increase in PPV to 15.38%. Further data are needed in order to evaluate the outcomes of CRMS/CFSPID after a long follow-up.